Analysis of the Capture Output on Flat Panel Detector using Arduino-Based BPW34 Photodiode Sensor with mA and kV Setting Parameters - Amin, M. R.; Wahyudi, M. F.; Mak’ruf, M. R.; Indrato, T. B.; Pudji, A.; Palanisamy, S. (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2022)
The exposure factor is the factor that determines the intensity and quality of X-rays received by the patient. Exposure factors that can be controlled are tube voltage (kV), tube current (mA), irradiation time (second), and distance of the X-ray tube to the film (FFD). The purpose of this study was to capture X-rays at a relatively affordable manufacturing price and to obtain different value from the detector's capture between dark and light by utilizing the response of the BPW34 photodiode sensor. The contribution of this study is that the system can display grayscale and numerical on an 8x8 pixel matrix using the Matrix Laboratory (MATLAB) Application. This study was able to convert images taken from analog data after taking measurements on X-rays. The measurements were carried out by 2 methods, the range used was 32-63 mA with a tube voltage of 50 kV at an irradiation duration of 1 second and 50 - 70 kV with a tube current of 40 mA and an irradiation duration of 1 second. Based on the measurement results, the comparison between the Flat Panel Detector Design Tool and the Philips brand Digital Radiography obtained that the latter was able to respond to differences in dose and object thickness. The results of this study indicated that this tool could be used to capture X-rays so that the degree of blackness of the film were obtained